ADVERSE DRUG REACTIONS OF BACLOFEN, NALTREXONE, AND ACAMPROSATE IN PATIENTS HAVING ALCOHOL DEPENDENCE: A CROSS-SECTIONAL PHARMACOVIGILANCE STUDY - PANDHARE, SUDHIR PANDURANG; GOSAVI, DEVESH; KUMAR MISHRA, KSHIROD; SATHE, HARSHAL SHRIRAM (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The research aims to investigate the prevalence and patterns of adverse drug reactions (ADRs), gauge the severity of these reactions, establish causality in ADR cases, and assess the preventability of such adverse reactions. Methods: ADR information was gathered through personal interviews with patients or their relatives. Causality was assessed using the Naranjo algorithm, and a modified Hartwig and Siegel Severity Assessment Scale was used for estimating the severity of ADR. ADRs were grouped into various preventability categories based on the modified Schumock and Thornton criteria. Results: The total number of patients evaluated in the baclofen, naltrexone, and acamprosate groups was 65, 28, and 42, respectively. The most commonly reported adverse events with baclofen were nausea (31.25%), followed by fatigue (18.75%) and headache (12.50%). The majority of patients receiving acamprosate reported nausea (57.14%), followed by diarrhea (28.57%). Patients receiving naltrexone most commonly reported nausea (35.71%), followed by abdominal pain (21.43%) and headache (14.28%). Conclusion: This study shed light on the prevalence, severity, causality, and preventability of ADRs associated with anti-craving agents used to treat patients with alcohol withdrawal syndrome, providing valuable insights into the safety profiles of these medications.